Beltraneja - Montero, Juan (Academia Peruana de la Lengua, 2020)
This is a critical edition of an anonymous satire produced in Perú under the viceroyalty of the Count of Lemos. The text, a mock-epic, narrates the defeat of the English corsair Richard Hawkins by the Peruvian fleet, while poking fun at all members of the court. This is the first critical edition of the work following neolachmannian methodology.